2016
DOI: 10.1038/sc.2016.109
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease and hypertension in a non-selected spinal cord injury patient population

Abstract: The prevalence of CAD, HT and some of their risk factors after SCI is generally, but not consistently and not statistically significant, slightly higher than in the corresponding general population. The challenge is to reduce the prevalence of atherosclerotic morbidity after SCI below that in the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…17 Patients whose blood pressure values were greater than or equal to 140/90 mmHg or those who were taking antihypertensive medication according to their medical records were classified as hypertensive. 18 Persons who smoked or used smokeless tobacco daily until within 1 year of the interview were considered current daily smokers and daily tobacco users. Never smokers were those who responded with "occasionally" or "not at all" on the questionnaire, and ex-smokers were those who smoked daily prior to 1 year of interview.…”
Section: Data Collectionmentioning
confidence: 99%
“…17 Patients whose blood pressure values were greater than or equal to 140/90 mmHg or those who were taking antihypertensive medication according to their medical records were classified as hypertensive. 18 Persons who smoked or used smokeless tobacco daily until within 1 year of the interview were considered current daily smokers and daily tobacco users. Never smokers were those who responded with "occasionally" or "not at all" on the questionnaire, and ex-smokers were those who smoked daily prior to 1 year of interview.…”
Section: Data Collectionmentioning
confidence: 99%
“…During treatment, multiple system complications could occur, including respiratory failure, pneumonia, bedsores, urinary tract infection (UTI), thromboembolic diseases, and cardiovascular accidents (Maharaj et al, 2016). The incidence of coronary atherosclerotic heart disease (CHD) caused by abnormal lipid metabolism after SCI is as high as 12%, which is significantly higher than that of the general population (6%) (Aidinoff et al, 2017). Current serum lipid analysis shows that TC, LDL-c, VLDL-p, LDL-c, and TG are elevated, while HDL-c is reduced in patients with SCI (Koyuncu et al, 2017;La Fountaine et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The following year, La Fountaine et al [ 101 ] identified that a lower triglyceride cutoff value was associated with dyslipidemia in people with SCI (115 mg/dL in SCI above T4 and 137 mg/dL in SCI below T5) than in people without SCI. Similarly, in another study, people with injuries below T6 had a higher rate of hypercholesterolemia than people with SCI above T7 [ 102 ]. These studies suggest that male gender and level of injury are unmodifiable cardiovascular risk factors ( Figure 1 ), and standard cutoffs for hypertriglyceridemia may be inappropriate for SCI.…”
Section: Dyslipidemia After Scimentioning
confidence: 92%